STRESSANDSTRAIN RECONSTRUCTION FOR THE EASTERN SEGMENT OF THE BALTIC SHIELD - Lidia A. Sim; Dmitry V. Zhirov; Anton V. Marinin (Геодинамика и тектонофизика)
The publication presents stress determinations from geological and kinematical indicators of tectonic stress fields, varying in ranks, for the Kola Peninsula. The objective is to determine possible mechanisms of formation of recent structures in the eastern segment of the Baltic shield and to forecast seismogenic and technogenic hazard of fracturing.The study is focused on the Kovdor and Khibin Paleozoic alkaline-ultrabasic blocks. Tectonic stresses are reconstructed by M.V. Gzovsky’s method [1954; 1975] based on identification of conjugated shear systems. Neotectonic stresses are studied by the kinematic method [Gushchenko, 1979] on the basis of measurements of tectonic displacment vectors from slickensides (Figure 2). Local stress data processed by the method for determination of general stress fields provide for reconstruction of main normal stresses which are arbitrarily considered as regional stresses [Sim, 1980; 2000]. This study uses the method of bandpattern distribution of fracturing in fault zones [Danilovich, 1961] which determines the main displacement line on the fault plane.The study of the Zhelezny mining site (Kovdor block, Figures 3 and 4) revealed that elements of fractures of two different ages (centroclinal fractures of the prototectonic genesis and fractures of later tectonic activation) are spatially overlapping due to rock collapse and lacking stability of benches. Numerous inversions and changes of kinematics of relative displacements were reviewed. It was observed that the southeastern wall of the quarry collapsed due to local extension (Fig. 6Band Photos 1 and 2), and a large fault, i.e. a prototectonic fracture, was dipping towards the quarry. Based on the analyses of local stresses at various points of the quarry (Table 1), two ‘regional’ stress fields can be revealed (Figures 7 and 8). The first paleostess field was associated with reverse faults of the WNW subhorizontal axis of compression and the steeply dipping axis of extension. The second field was related to shear faults; its axis of compression maintained the WNW orientation, while the extension axis was reoriented, and the axis of extension attained submeridional position and a less steep dip. The second field is younger as suggested by traces of two displacements identified on several planes, the youngest of which are shears.From the analysis of measurements taken at 273 planes with striations, it is evident that striations are distributed in a bandshape pattern. The band of fractures is coincident with the plane of the transition axis of the young ‘regional field (Figure 9); main maximums of density of the planes with striations are symmetrically scattered in a fanlike pattern from the axis of compression and extension of this field. Generally, the striations reflect traces of younger displacements, and their consistency with the axes of the young field supports our conclusions on age relationships between  the two ‘regional’ fields. Four major stages of deformation of the Kovdor block under study are distinguished by analyses of the tectonic stresses (Figure 10).Within the limits of the Khibin block, 14 local states of stresses are reconstructed for three mining sites (Table 2, Figure 11). At the Central mining site, reindexation of local axis of compression and extension in the fault wings give evidence of the fault activity during the neotectonic stage (Figure 13). The ‘regional’ stress field of the Khibin block is associated with a reserve fault with lowangle NNW orientation of the axis of compression (Figure 14). The tectonophysical studies conducted at the mining sites of the Kola Peninsula give grounds to conclude that activity of faults, which positions are different at the mining sites, is variable, depending on orientations of the faults against the youngest ‘regional’ main stress. From sets of indicators, a relative age of the revealed ‘regional’ fields of stresses is accepted as neotectonic and recent.For the segments of the Kovdor block under study, four phases of deformation are distinguished, including two early phases revealed by structural indicators, and two last phases revealed from orientations of the axes of the main stresses in the reconstructed ‘regional’ fields. The reverse field of stresses of Deformation Phase 3 (which is a more ancient ‘regional’ field according to reconstructed tectonic stresses) at the Kovdor block and the reversefault field at the mining sites of the Khibin block may reflect a phase of brittle deformation of the rocks after the blocks were exposed to the day surface. Since then the deformation mechanisms might have been determined by two factors which controlled subhorizontal compression: residual gravity stresses in considerably eroded magmatic bodies as ‘recollections’ of being subject to constraint environment at depth [Rebetsky, 2008], and the impact of rifting in the Northern Atlantics. The fact that the neotectonic ‘regional’ stress field of the Kovdor block is fully similar to that of the Central Karelia (Figure 1) give grounds to conclude that the mechanism of deformation of the block under study might have been controlled by both factors. The Khibin block has a lopolithic shape which gradually converts into a centraltype conic structure with depth. It should thus be squeezed upward by the impact of horizontal compression of any genesis, as evidenced by the subvertical extension axis of the general field of the Khibin area and the recent topography as the highest mountains of the Kola Peninsula are located in the block under study.